2021
DOI: 10.1186/s13287-021-02161-8
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes derived from miR-301a-3p-overexpressing adipose-derived mesenchymal stem cells reverse hypoxia-induced erectile dysfunction in rat models

Abstract: Background Erectile dysfunction (ED) has often been observed in patients with obstructive sleep apnea (OSA). Research on adipose-derived mesenchymal stem cell (ADSC)-derived exosomes has shown that they have significant therapeutic effects in many diseases including ED. Methods In this study, ED was induced in Sprague Dawley (SD) rats using chronic intermittent hypoxia (CIH) exposure. CIH-mediated influences were then measured in the corpus caverno… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 45 publications
(45 reference statements)
0
21
0
Order By: Relevance
“…THE modified strategies for enhancing loading and targeted delivery of EVs have been reported. Engineering EVs were mostly carried out either via transfecting functional molecules into ASCs [ 14 , 17 , 21 , 26 , 34 , 35 , 44 , 45 , 49 , 72 , 77 , 79 , 82 , 113 , 125 , 181 ] or directly transfecting functional molecules into EVs [ 22 , 37 , 142 ]. Six studies [ 20 , 67 , 85 , 86 , 102 , 103 ] reported the strategy of hypoxia culture precondition of ASCs.…”
Section: Resultsmentioning
confidence: 99%
“…THE modified strategies for enhancing loading and targeted delivery of EVs have been reported. Engineering EVs were mostly carried out either via transfecting functional molecules into ASCs [ 14 , 17 , 21 , 26 , 34 , 35 , 44 , 45 , 49 , 72 , 77 , 79 , 82 , 113 , 125 , 181 ] or directly transfecting functional molecules into EVs [ 22 , 37 , 142 ]. Six studies [ 20 , 67 , 85 , 86 , 102 , 103 ] reported the strategy of hypoxia culture precondition of ASCs.…”
Section: Resultsmentioning
confidence: 99%
“…The same group in 2015 demonstrated that endoplasmic reticulum stress-related cell apoptosis is involved with low levels of constitutive NOS and NO in rats ( 44 ). Recently, Liang et al ( 45 ) showed that exosome treatment significantly improved erectile function in LTIH exposure-induced ED rats and corpus cavernous smooth muscle cells (CCSMCs) by inhibiting apoptosis and promoting autophagy, which were associated with the PTEN/hypoxia-inducible factor-1 alpha (HIF-1α) and Toll-like receptor 4 (TLR4) signaling pathways.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, the overexpression of PTEN or TLR4 reverses the therapeutic effects of miR-301a-3p in CCSMCs, indicating that miR-301a-3p modulates PTEN/HIF-1α/TLR4 signaling, autophagy and apoptosis for the treatment of ED. However, the cross-talk of PTEN/HIF-1α/TLR4 signaling and autophagy remains to be further investigated in ED ( Liang et al , 2021 ).…”
Section: Clinical Impact Of Autophagy On the Fate Of Spermmentioning
confidence: 99%